Optimization by Using Taguchi Method of the Production of Magnesium-Matrix Carbide Reinforced Composites by Powder Metallurgy Method - Özkan Küçük; Tayeb Taher Kalefe Elfarah; Serkan Islak; Cihan Özorak (MDPI AG, 2017)
The aim of this study was to determine the optimum production parameters in the production of magnesium matrix carbide-reinforced composites by using the powder metallurgy method. The parameter levels maximizing density (%), hardness (HB10), and bending strength (MPa) values were found by using the Taguchi method. The type of reinforcement, the amount of reinforcement, the sintering time, the sintering temperature, additive type, and additive rate were selected as the production parameters. Since the production of Mg and its alloys by using casting methods is problematic, the hot pressing method, a powder metallurgy method, was preferred in this study. Ceramic-based carbide particles were used as reinforcing materials in Mg matrix composite materials. B4C, SiC, Mo2C, and TiC carbides were preferred as the carbide. Microstructure and phase composition of the produced materials was examined with scanning electron microscope (SEM), X-ray diffractogram (XRD) and X-ray energy dispersive spectrometry (EDS). The hardness of the materials was measured by using a Universal Hardness device. The relative densities of the materials were determined according to Archimedes’ principle. The bending strength properties of the materials were determined by using the three-point bending test. The optimum conditions were a sintering temperature of 500 °C, sintering duration of 5 min, additive type of B4C and additive rate of 2.5%, and the results obtained at these conditions were found to be as follows; relative density of 98.74 (%), hardness of 87.16 HB10 and bending strength of 193.65 MPa. SEM images taken from the fracture surfaces showed that the carbides added to the matrix had a relatively homogeneous distribution. XRD analyses revealed that the matrix was oxidized very little, and no phase formation occurred between the matrix and the carbides. Carbide addition caused a distinct hardness increase by showing the effect of distribution strengthening in the matrix.
Keywords: Mining engineering. Metallurgy; taguchi method; taguchi method; optimization; metal matrix composites; microstructure; microstructure; TN1-997; optimization; metal matrix composites